(untitled) (Marketing Journal, 2025)
in this article, management approaches to regional resource management are scientifically analyzed on the basis of institutional theory and economic security indicators. The economy of the region is directly related to the level of effective use of resourc es, and natural, labor, financial and productive resources are considered as the main factors of economic security. In recent years, there have been imbalances in resource management in the processes of Territorial Development, low efficiency and insuffici ent functioning of institutional mechanisms. In this context, this study offers the use of institutional economics approaches in regional resource management as well as the use of indicators such as Gini, Theil, Atkinson and Hoover in economic security assessments. The analysis carried out on the example of the regions of Uzbekistan reveals the connection between the efficiency of resource use and economic security. Based on the results of the study, scientifically based recommendations are developed aimed at improving regional management, rational use of resources and reducing territorial differences.